Caracterização estrutural e magnética de cromitas produzidas pelo método de coprecipitação - Gurgel, Thiago Targino (2016)
Polycrystalline samples Mn1-xZnzCr2O4 and Cu1-xNixCr2O4 (0 x 1; 0) were produced by co-precipitation method and treated at temperatures of 400oC and 1200oC. The samples have been investigated by dc/ac magnetization as a function of temperature and magnetic field. In addition, Xray powder diffraction, X-ray fluorescence and scanning electron microscopy measurements were carried out at room temperature. The analysis results of X-ray diffraction showed that the materials are single phase. The structural refinement was carried out by the Rietveld method and cell parameters determined for these materials are consistent with those reported in the literature for bulk samples. The average particle sizes were calculated using the equation of Scherrer and compared to the sizes obtained by scanning electron microscopy. It is observed that these spinel particles have an average size of 18-55 nm. It is noted an increase in the average size with increasing calcination temperature. We study the evolution of the magnetic properties of normal spinels of the series Mn1-xZnzCr2O4 and Cu1-xNixCr2O4 through magnetic measurements with magnetometer PPMS-9T (Physical Property measurement system). Normal spinels CuCr2O4 and MnCr2O4 are ferromagnetic with Curie temperature 122 K and 43 K respectively. The zinc chromite (ZnCr2O4) which in its nano-form features an antiferromagnetic ordering with Néel temperature (TN) of 5 K, the NiCr2O4 shows two magnetic transitions, one at TC 75K related to a ferromagnetic component (longitudinal) and the second the TS 30K, associada a componente antiferromagnética (transversal). The magnetization in the system Mn1-xZnxCr2O4 for 0 x 0:5 indicates characteristics of an antiferromagnetic ordering (AF), while values of x 0:6 define the system with a typical ferrimagnetic order (FI). The behavior at the borders of AF / FI phase is indicated by the appearance of coercive field in hysteresis loops and two temperatures magnetic order. However, for other series of chromite spinel Cu1-xNixCr2O4, with x 0:5, the compounds are ferrimagnetic. In the range of 0:5 x 1:0 arise two magnetic transitions with an increased coercive field which may be associated with the emergence of components (FI) and (AF). The hysteresis cycles of the samples are clearly asymmetric, and this behavior can be attributed to the originating exchange bias effect of the presence of a ferrimagnetic and antiferromagnetic layer in the samples. In the present study we show the results of the magnetic properties of spinel chromite Mn1-xZnzCr2O4 and Cu1-xNixCr2O4 (0 x 1; 0) on a nanometric scale and bulk.EMC was investigated in three spinel type samples, when data are obtained by the measurement magnetization as function of temperature and found the change of entropy of each of them, we observe the change in the magnetic transition temperature with the applied magnetic field, but we noted not large EMC intensity values.